Pollution in infographics - Lowe, Alexander (Enviro-graphics., 2021)
Presents information about pollution through a collection of diagrams and charts. Discusses different types of pollution, the dangers of pollution, and ways to help stop pollution. Includes an activity, a glossary, and resources for further information.